Reduction of Systolic and Diastolic Blood Pressure in Hypertensive Elderly Following Ergonomic and Isometric Handgrip Exercises - Rohmana, Omay; Rochayat, Ati Siti; Iskandar, Asep (Jurnal Keperawatan Soedirman, 2025)
The largest population in Indonesia suffering from hypertension in 2023 is the elderly. Ergonomic and isometric handgrip exercises are recommended for managing hypertension. The aim of this study was to investigate the differences in systolic and diastolic blood pressure among hypertensive elderly individuals. The research design was a pre- and post-intervention experimental approach with two treatment groups. The study population consisted of hypertensive elderly individuals in Cirebon, Indonesia. The samples size was calculated using formula (t-1) (r-1) > 15 for each group, resulting in a total of 32 hypertensive elderly, selected through simple random sampling. Data analysis was conducted using a parametric t-test. The results indicated a significant difference in systolic (p=0.024 < 0.05) and diastolic (p=0.045 < 0.05) blood pressure between the isometric handgrip exercise and ergonomic exercise groups following the intervention. Ergonomic exercise yielded a more significant results, with a reduction of 15.3 mmHg in systolic pressure and 10.0 mmHg in diastolic pressure, compared to the isometric handgrip exercise, which resulted in reductions of 5.75 mmHg in systolic pressure and 4.0 mmHg in diastolic pressure. Ergonomic exercise can be recommended as a safe and accessible form of exercise for hypertensive elderly individuals.